A meta-analysis of obesity and the risk of pancreatic cancer. - Berrington de Gonzalez, A; Sweetland, S; Spencer, E (2003)
Smoking and diabetes are the only established risk factors for pancreatic cancer. Findings from recent studies suggest that obesity may also be associated with an increased risk of pancreatic cancer, but several earlier studies were less conclusive. We examined this relationship in a meta-analysis of published data. Six case-control and eight cohort studies involving 6391 cases of pancreatic cancer were identified from a computer-based literature search from 1966 to 2003. The relative risk per unit increase in body mass index was estimated for each of the studies from the published data. In a random effects model, the summary relative risk per unit increase in body mass index was 1.02 (95% CI: 1.01-1.03). There was some evidence of heterogeneity between the studies' results (P=0.1). The summary relative risk estimates were slightly higher for studies that had adjusted for smoking and for case-control studies that had not used proxy respondents. The estimated per unit increase in body mass index would translate into a relative risk of 1.19 (95% CI: 1.10-1.29) for obese people (30 kg m(-2)) compared to people with a normal body weight (22 kg m(-2)). These results provide evidence that the risk of pancreatic cancer may be weakly associated with obesity. However, the small magnitude of the summary risk means the possibility of confounding cannot be excluded.